Principal Leadership Based on IMTAQ in Improving Student Achievement - Mawerdeh, Mawerdeh; Jalili, Abdul; Musthofa, Indhra (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This research is motivated by the urgent need for a school leadership model capable of integrating the values of Faith and Piety (IMTAQ) with student achievement improvement in the modern era, which tends to emphasize cognitive aspects. The purpose of this study is to analyze and deeply understand the principal's leadership practices in implementing an IMTAQ-based vision at Al-Khatibiyah Senior High School in Bangkalan. The research approach employs a qualitative method with an intrinsic case study design focusing on the specific context of one Islamic educational institution. Data were obtained through semi-structured interviews, participatory observation, and documentation study, and validated through source and method triangulation. The research results show that the principal implements spiritual transformational leadership through moral exemplification, participatory involvement, and the ability to inspire school members to internalize IMTAQ values. Flagship programs such as Musabaqah Hifdzil Qur'an (MHQ), religious studies, and the integration of religious values in learning have proven to contribute to improving students' academic achievement and character. The novelty of this research lies in strengthening the concept of IMTAQ-based spiritual transformational leadership that integrates religious, pedagogical, and managerial dimensions comprehensively.